Evaluating competition, interactions and trait differences between vulnerable marine ecosystem taxa in climate changing ocean: laboratory studies on flow and feeding responses by gorgonians (Condor seamount) and cold-water scleractinian corals, sponges and bivalves (Norwegian shelf). - Liefmann, Stephanie (The University of Edinburgh, 2021)
Cold-water corals reefs, gardens and sponge grounds are vulnerable marine ecosystems (VMEs) as defined by UN resolution 61/105. These VMEs are protected from destructive fishing practices and are recognised due to the biodiversity they support. However, despite such international policy imperatives, we lack even basic understanding of ecological interactions between VME indicator taxa. For example, we do not understand how co-occurring VME indicator species interact or compete with each other under different conditions, such as water flow and food concentrations, both of which are likely to change in direct response to climate change. This thesis aimed to evaluate competition and trait differences underlying VME indicator species. Taxa co-occurring in 2 different VMEs were tested under laboratory conditions. From the Condor Seamount (Azores archipelago) the octocorals Viminella flagellum and Dentomuricea meteor, were compared according to two traits: skeletal composition and sclerite shape and size. Viminella flagellum and D. meteor were also tested for competition interactions under 2 different flow regimes. From the Norwegian continental shelf, feeding efficiency, particle size and type preference under varying flow and natural food conditions was measured for species with different feeding strategies/traits (active and passive suspension feeders). The tested species include a scleractinian coral (Lophelia pertusa), demosponges (Geodia barretti, Phakellia ventilabrum and Stryphnus sp.) and a bivalve (Acesta excavata). The different traits found in co-occurring species can represent different strategies permitting them to exploit and withstand the variable a-biotic and food supply conditions, meaning they can niche partition. Differences in feeding efficiency are more evident when comparing across taxa than individual species, reinforcing that trait differences are crucial and should be taken into consideration. Trends suggest that different species have preferences for different subsets of the natural occurring seston, which could be mediated by the different traits. Understanding the preferences of different species, and relating them to the predicted changes in food composition availability and flow changes will help refine future species distribution models and ecosystem functioning of VMEs in a changing ocean. Evidence highlights how exclusive competition could occur under specific conditions between the study species. The findings suggest other interactions besides competition should be taken into account when studying coexisting species, for example facilitating cascades and nutrient recycling. Species interactions should be taken into account when performing species distribution models in order to better predict the effect of changing conditions in ecosystem functioning.